Hubungan Sikap, Pola Kerja, dan Sedentary Lifestyle dengan Kejadian Hipertensi pada Nelayan di Kelurahan Bagan Deli Kota Medan: Penelitian - Dya Astrid Hidayah; Alam Bakti Keloko; Rusmalawaty; R.Kintoko Rochadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs), particularly hypertension as a silent killer, are a major global health threat with the highest mortality rates. According to the 2018 Basic Health Research, the prevalence of hypertension in Indonesia reached 34.1%, and 29.2% in North Sumatra. In 2023, North Sumatra recorded 3,287,526 hypertension cases among individuals aged ≥15, yet only 18.61% received healthcare services. Medan had the highest number of cases (478,092) with low service coverage (9.43%). In 2024, Bagan Deli Subdistrict in Medan reported 457 cases, with most residents working as fishermen. This study aims to examine the relationship between attitudes, work patterns (including working hours, fatigue, sleep quality, smoking habits), and sedentary lifestyle with hypertension incidence among fishermen. A quantitative method with a cross-sectional approach was used on 95 respondents selected via accidental sampling. Data were analyzed using the chi-square test. Results showed significant relationships between hypertension and attitude (ρ=0.008), working hours (ρ=0.038), and fatigue (ρ=0.017). No significant relationships were found with sleep quality (ρ=0.488), smoking (ρ=0.057), or sedentary lifestyle (ρ=0.319). These findings may support the development of more effective hypertension prevention programs in coastal fishing communities.